HOW WORK SATISFACTION AND ORGANIZATION CLIMATE INFLUENCE ORGANIZATIONAL CITIZENSHIP BEHAVIOUR - Arissetyanto Nugroho; Elyssa Nurulita; Janfry Sihite (MIX: JURNAL ILMIAH MANAJEMEN, 2020)
The research explores the influence of job satisfaction and organizational climate on organizational citizenship behavior. The object of this research are employees at PT.CCM. The research conducted to 60 respondents by delivering a questionnaire. The data analysis conducted with multiple linear regression tests. The result of this research shows that there is a partially and simultaneously correlation between job satisfaction and organizational climate toward organizational citizenship behavior.